2007
DOI: 10.1080/09537100701481385
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and human platelet GP IIb/IIIa receptor activation

Abstract: This study concerned reactive oxygen species for their potential to activate human platelet GP IIb/IIIa receptors. All cells produce reactive oxygen species - radicals that can abstract electrons and hydrogen atoms from biological molecules to alter cell function. In many cells, radicals contribute to cellular signaling. In platelets, the predominant oxidant effect is platelet activation. Less is known concerning oxidants and GP IIb/IIIa receptor activation. The first aim of the current study was to confirm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
3
12
0
1
Order By: Relevance
“…The concentrations of X/XO used in the current study are consistent with similar studies [24] and there are many reports in the literature which demonstrate that ROS derived either from platelets [25], from damaged red blood cells [26] or from addition of freeradical generating systems [27], can augment platelet aggregation in response to stimulating agents such as collagen and ADP. In this study, we found that whole blood aggregated more readily in response to collagen, suggesting that other cell types present in whole blood may contribute to platelet aggregation.…”
Section: Discussionsupporting
confidence: 77%
“…The concentrations of X/XO used in the current study are consistent with similar studies [24] and there are many reports in the literature which demonstrate that ROS derived either from platelets [25], from damaged red blood cells [26] or from addition of freeradical generating systems [27], can augment platelet aggregation in response to stimulating agents such as collagen and ADP. In this study, we found that whole blood aggregated more readily in response to collagen, suggesting that other cell types present in whole blood may contribute to platelet aggregation.…”
Section: Discussionsupporting
confidence: 77%
“…Second, dogs were randomized to receive either intravenous dopamine 8 mgÁkg 21 Ámin 21 or epinephrine 0.2 mgÁkg 21 Ámin 21 (positive controls) and measurements repeated for 20 minutes. (Epinephrine 0.2 mgÁkg 21 Ámin 21 has been shown to increase spontaneous CFRs frequency and magnitude 14,26 ). Dopamine 8 mgÁkg 21 Ámin 21 dose was used because, when examined in a 4 dog's pilot study, this infusion rate approximately evoked the heart rate, arterial pressure, and cardiac index effects of epinephrine 0.2 mgÁkg 21 Ámin 21 .…”
Section: Acute Circumflex Coronary Artery Thrombosis In Anesthetized mentioning
confidence: 98%
“…Frequency and magnitude of these cycles are regarded as a semiquantitative measure of ongoing thrombosis. 14,25,26 CFR measurements were made during 4 periods in a crossover manner. First, spontaneous CFRs were assessed during 20-minute baseline control conditions.…”
Section: Acute Circumflex Coronary Artery Thrombosis In Anesthetized mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the present study did not investigate the effect of extracts on platelet aggregation, it is known that ROS may play, along with nitric oxide, adenosine and prostacyclin, a profound role in platelet activation by scavenging nitric oxide (which has a preventive effect on platelet aggregation), triggering tyrosine phosphorylation of β3 or supporting the metabolism of collagen and arachidonic acid [23]. Considering that primary mechanism of tBHP action is generation of oxidative stress [45] and that tBHP has been previously demonstrated to support platelet activation cascade [46], it is plausible that the antioxidant properties of mushroom extracts may also prevent platelets from aggregation. Moreover, a recent study demonstrated that an extract of P. eous inhibited human platelet activation in vitro, the effect linked to the high mushroom content of phenolic compounds and flavonoids [47].…”
Section: Antioxidant Activity Of Bio-enriched Mushroomsmentioning
confidence: 99%